2019
DOI: 10.1186/s13317-019-0110-z
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of TSLP and IL-33 cytokines in ulcerative colitis

Abstract: PurposeInflammatory bowel disease (IBD) primarily includes ulcerative colitis (UC) and Crohn’s disease (CD). Thymic stromal lymphopoietin (TSLP) is a cytokine produced by intestinal epithelial cells (IECs) with immunomodulatory properties that plays an important role in the development of regulatory T cell (Treg) responses and tolerance in the gut. On the other hand, IL-33 has been considered as a cytokine with two different properties, inflammatory and anti-inflammatory functions, the latter may play a protec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 29 publications
0
20
0
1
Order By: Relevance
“…Our results suggest that EPS L and laminarin exhibit normal values of gene expression, leading to a balanced TSLP function, while EPS P slightly decreases its expression, and probably has no effect on TSLP turn over. EPS P fold change reached 0.74, which means that the decrease of relative expression is not so dramatic as expected in CD patients with active inflammatory reactions (Tahaghoghi-Hajghorbani et al, 2019).…”
Section: Effect Of O2-substituted-(1-3)-β-d -Glucans On Gene Expressi...mentioning
confidence: 54%
See 1 more Smart Citation
“…Our results suggest that EPS L and laminarin exhibit normal values of gene expression, leading to a balanced TSLP function, while EPS P slightly decreases its expression, and probably has no effect on TSLP turn over. EPS P fold change reached 0.74, which means that the decrease of relative expression is not so dramatic as expected in CD patients with active inflammatory reactions (Tahaghoghi-Hajghorbani et al, 2019).…”
Section: Effect Of O2-substituted-(1-3)-β-d -Glucans On Gene Expressi...mentioning
confidence: 54%
“…In IBD patients, low levels of TSLP are associated with a permeability increase of the gut barrier, or Th2 cell differentiation, depending on the cell type that is expressing it (epithelial cells or DC cells; Biancheri et al, 2016;Park et al, 2017). Recently, it has been proposed that TSLP also participate in Treg cell development and gut homeostasis perpetuation (Tahaghoghi-Hajghorbani et al, 2019). Our results suggest that EPS L and laminarin exhibit normal values of gene expression, leading to a balanced TSLP function, while EPS P slightly decreases its expression, and probably has no effect on TSLP turn over.…”
Section: Effect Of O2-substituted-(1-3)-β-d -Glucans On Gene Expressi...mentioning
confidence: 99%
“…a number of previous studies have demonstrated an important role for TSlP in different diseases (17,18). Blocking the binding of TSlP to TSlPr may inhibit TSlP signalling, which may provide a therapeutic strategy to treat various diseases (19).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, they showed that IL-4 and TNF-α may exacerbate TSLP expression, leading to enhanced inflammation [ 88 ]. However, others showed that TSLP was reduced in UC patients compared with healthy or non-inflamed tissues [ 89 , 90 ]. Patients receiving anti-IL-13 (tralokinumab) also showed more TSLP transcriptional expression with improved tissue healing compared before treatment [ 89 ].…”
Section: Epithelium-derived Type 2 Immunity Associated Cytokinesmentioning
confidence: 99%